Effect of a 6-Week Active Play Intervention on Fundamental Movement Skill Competence of Preschool Children - Gareth Stratton (Perceptual and Motor Skills, 2017)
This study examined the effectiveness of an active play intervention on fundamental movement skills among 3- to 5-year-old children from deprived communities. In a cluster randomized controlled trial design, six preschools received a resource pack and a 6-week local authority program involving staff training with help implementing 60-minute weekly sessions and postprogram support. Six comparison preschools received a resource pack only. Twelve skills were assessed at baseline, postintervention, and at a 6-month follow-up using the Children’s Activity and Movement in Preschool Study Motor Skills Protocol. One hundred and sixty-two children (Mean age = 4.64 ± 0.58 years; 53.1% boys) were included in the final analyses. There were no significant differences between groups for total fundamental movement skill, object-control skill or locomotor skill scores, indicating a need for program modification to facilitate greater skill improvements.